Design of optimised multi-scale structures for multifunctional composites - Lee,C; Panesar,A; Greenhalgh,E (Engineers Australia, 2019)
The multi-scale structures are commonly found in nature, such as plants and bones. Such multi-scale structurescan be divided into macro-scale, micro-scale and further sub-scale structures. In this study, we aim to designoptimised two-scale structures for multifunctional composites, specifically by enhancing the structural stiffnessand the ionic conductivity simultaneously. To tackle this problem, a novel strategy for achieving optimised multiscale structures is presented. A database of optimised micro-scale structures and simple placement criterion forthe micro-scale structure were applied. We demonstrate the efficiency of our strategy by designing, optimisingand evaluating two-scale structures composed of macro-and micro-scales. The advantage of our strategy foroptimised multi-scale structures is presented and discussed by comparing the structural stiffness and the ionicconductivity of several two-scale structures composed of different microstructures such as the solid-void, uniformand varied microstructures.